Influence of post harvest processing conditions on yield and quality of ground turmeric (Curcuma longa L.) - Maria Lúcia A. Bambirra; Roberto G. Junqueira; Maria Beatriz A. Glória (Brazilian Archives of Biology and Technology, 2002)
Studies were carried out to evaluate the influence of post harvest processing conditions on yield and quality of ground turmeric. Rhizomes were peeled, cooked (autoclave or immersion) in water or alkaline media, sliced, dehydrated, ground, sieved, packaged in polyethylene bags and stored for 60 days at room temperature. Yields ranged from 9.84 to 14.51 g of powder/100 g of rhizome with moisture varying from 8.84 to 9.86 g/100 g. Peel removal caused 30% mass loss but the powder obtained had higher intensity of yellow and red. Cooking caused a reduction in dehydration time and provided a powder with lower moisture content, higher levels of curcuminoid pigments and higher Hunter CIE L*, a* and b* values. Cooking by immersion provided higher quality powder compared to autoclave. Use of alkaline media resulted in a product with lower curcuminoid content, and higher intensity of yellow. There was no change in pigment and colour characteristics during storage. A influência do processamento no rendimento e na qualidade da cúrcuma em pó foi investigada. Os rizomas foram descascados, cozidos (autoclave ou imersão) em água ou meio alcalino, fatiadas, desidratadas, moídas, peneiradas, embaladas em polietileno e armazenadas por 60 dias à temperatura ambiente. O rendimento variou de 9,84 a 14,51 g de pó/100 g de rizoma com teores de umidade de 8,84 a 9,86 g/100 g. A remoção da casca causou perda de 30% de massa mas o pó obtido apresentou maior intensidade de amarelo e vermelho. O cozimento causou uma redução no tempo de secagem e forneceu um pó com menor teor de umidade, maiores teores de pigmentos curcuminóides e maiores valores de Hunter CIE L*, a* e b*. O cozimento por imersão forneceu um pó de melhor qualidade comparado àquele por autoclave. O uso de meio alcalino resultou em um produto com menor teor de pigmentos curcuminóides, e maior intensidade de amarelo. Não foi observada alteração nos teores de pigmentos e nas características de cor do pó durante armazenamento.